Inserción de las psiquiatrías nacionales en el contexto de consolidación de la modernización latinoamericana: Primeras Jornadas Neuro-Psiquiátricas Panamericanas, Santiago de Chile, 1937 - Claudia Araya Ibacache (Nuevo mundo - Mundos Nuevos, 2014)
Between the 4th and the 11 of January 1937 the First Pan American Conference Neuro- Psychiatric took place in Santiago, sponsored by the Chilean government and the University of Chile. Medical alienists and neurologists attended this Conference from nine Latin American countries. The purpose of this article is to analyse the strategies proposed by the organizers and by those who attended the conference, in order to insert Latin American national psychiatries in the Western scientific development, at a time in which Europe was portrayed as suffering from a political and moral crisis, while Latin America expands and consolidates its modernization. Particularly in the case of Chile is a strong proposal to consolidate the scientific nature of psychiatry as a primary strategy for the conquest of mental illness and the legitimacy of the discipline. I also want to analyze the geopolitical networks begin to organize around the establishment of a psychiatric knowledge and the role they play in this flow paths of knowledge, and the mechanisms by which the legitimate psychiatric discourse: scientific societies and national and international conferences.